Engineered CpG‐Antigen Conjugates Protected Gold Nanoclusters as Smart Self‐Vaccines for Enhanced Immune Response and Cell Imaging. (20th September 2013) - Tao, Yu; Ju, Enguo; Li, Zhenhua; Ren, Jinsong; Qu, Xiaogang
<x xml:space="preserve">Abstract</x> A facile one‐pot synthesis of fluorescent AuNCs by using ovalbumin‐CpG oligodeoxynucleotides (ODNs) conjugates as the templates, which can elicit specific immunological responses, is demonstrated. Through dual‐delivery of protein antigen and CpG ODNs, the as‐prepared AuNCs can act as smart self‐vaccines to assist in generation of high immunostimulatory activity while simultaneously act as an imaging agent. The AuNCs‐based vaccines are not thought to have not been reported so far, making this platform the first example of the usage of AuNCs as effective vaccines. Furthermore, compared with the antigen, the immunostimulatory activity of the as‐prepared AuNCs can not only be retained, but also can be effectively enhanced. These findings suggest the AuNCs‐based vaccines may be utilized as safe and efficient immunostimulatory agents that are able to prevent and/or treat a variety of ailments.